Rancang Bangun Sistem Informasi Inventaris Barang pada Divisi Perencanaan Strategis dan Pelayanan Terminal Petikemas di PT. Pelabuhan Indonesia - Mohammad Hilal Monoarfa; Andika Purnama; Rouly Doharma (Jurnal Teknik Informatika dan Teknologi Informasi, 2026)
This study aims to design and develop a Goods Inventory Information System for the Strategic Planning and Container Terminal Services Division of PT Pelabuhan Indonesia. The inventory management process, which is still carried out using Microsoft Excel, has resulted in various problems, such as data recording errors, data duplication, delays in report generation, and difficulties in monitoring inventory effectively. These issues make inventory management less efficient and may hinder the company’s operational activities. The system development method used in this study is the System Development Life Cycle (SDLC) with the Prototype model. This method was chosen because it allows users to participate directly in the system development process, ensuring that user requirements can be identified and accommodated more effectively. Data collection techniques included observation, interviews, and literature review to obtain information regarding existing business processes and system requirements. The results indicate that the developed web-based inventory information system is capable of supporting the integrated management of incoming goods, outgoing goods, and item borrowing processes. In addition, the system can generate reports automatically, improve work efficiency, reduce recording errors, and facilitate real-time inventory monitoring.